2021
DOI: 10.36660/ijcs.20190149
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Tp-e interval, Tp-e/QT , and Tp-e/QTc Ratios and Coronary Artery Disease Spectrum and Syntax Score

Abstract: Atherosclerotic cardiovascular diseases are still major underlying reasons for all-cause morbidity and mortality worldwide. 1 While several factors have been described to explain the possible etiologic bases for mortality in the presence of coronary artery disease (CAD), ventricular arrhythmia is one the most important causes of catastrophic outcomes due to myocardial ischemia. 2 Coronary atherosclerosis can cause electrical heterogeneity in ventricular myocardium and ventricular repolarization abnormalities l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Helmy et al (11) observed a significant positive correlation between corrected QT dispersion and severity of coronary artery disease as assessed by SYNTAX score. Recently, Kahraman et al (12) found a strong and positive correlation between CAD severity as measured by SYNTAX score and prolonged Tp-e interval and increased Tp-e/QT and Tp-e/QTc ratios.…”
Section: Discussionmentioning
confidence: 99%
“…Helmy et al (11) observed a significant positive correlation between corrected QT dispersion and severity of coronary artery disease as assessed by SYNTAX score. Recently, Kahraman et al (12) found a strong and positive correlation between CAD severity as measured by SYNTAX score and prolonged Tp-e interval and increased Tp-e/QT and Tp-e/QTc ratios.…”
Section: Discussionmentioning
confidence: 99%
“…Expanded atherosclerosis may involve the ventricular myocytes and Purkinje system, leading to delay in conduction velocity and prolonged QRS [ 17 , 22 , 27 , 28 ]. New parameters related to QRS complex including fragmented QRS [ 27 , 29 ], R wave peak time [ 17 ], and ventricular repolarization indicators such as corrected QT dispersion [ 30 ], or Tp-e interval, Tp-e/QT, Tp-e/QTc ratios [ 31 ] have been introduced as predictors of high SYNTAX score. In contrast, our efforts to corroborate a significant association between QRS complex parameters with intermediate and high SYNTAX scores failed, except for the delayed QRS transition zone; to the best of our knowledge, this is the first study to show that the delayed QRS transition zone is an independent predictor of intermediate SYNTAX score.…”
Section: Discussionmentioning
confidence: 99%
“…During the retrospective cohort study, a total number of 876 patients were diagnosed with unstable angina. After applying the exclusion criteria, 600 patients were divided into tertiles based on the SYNTAX scores as low (0-22), intermediate (23)(24)(25)(26)(27)(28)(29)(30)(31)(32), and high (≥ 33). The association between ECG parameters and SYNTAX score was investigated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Atherosclerotic cardiovascular disorders continue to be a major source of all-cause morbidity and mortality around the world, with ventricular arrhythmias being the most prominent predictors of death [ 27 ]. In their study, Kahraman et al [ 27 ] showed that ventricular arrhythmic predictors (Tp-e interval, Tp-e/QT, and Tp-e/QTc ratios) increase as one progresses from normal coronary artery to acute coronary syndrome. Also, higher ventricular arrhythmic predictor values were related to more extensive coronary artery disease [ 28 ].…”
Section: Discussionmentioning
confidence: 99%